Type IV acromioclavicular joint dislocation associated with a mid-shaft clavicle malunion - Mohammed, Khalid D. (Int J Shoulder Surg, 2016)
This reports presents the case of a combined clavicle fracture malunion and chronic Type IV acromioclavicular (AC) joint dislocation. The patient was seen acutely in the emergency department following a mountain bike accident at which time the clavicle fracture was identified and managed conservatively however the AC dislocation was not diagnosed. The patient presented 25 months following the injury with persistent pain and disability and was treated with clavicle osteotomy and AC stabilization. We document the clinical details, surgical treatment and outcome.